The Construction of Interfaith Knowledge within a Family in Sukoreno Village, Jember Regency - Arifiyanti, Jati; Riko Try Hanuraga, Riko Try Hanuraga; Gita Isyanawulan, Gita Isyanawulan (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
Religious difference remains a sensitive issue in Indonesia, often becoming a source of social tension and conflict. In contrast, Sukoreno Village is characterized by its religious diversity and relatively harmonious interfaith relations. This study aims to analyze the construction of interfaith knowledge within a family living in Sukoreno Village. The phenomenon is examined through the lens of Social Construction Theory as developed by Peter L. Berger. This research adopts a qualitative method with a constructivist approach. The findings indicate that religious diversity has become a normalized aspect of family life in the village, forming a social reality that has been sustained across generations. This reality emerges through a process of knowledge construction that involves the stages of externalization, objectivation, and internalization. Furthermore, religious difference within the family setting gives rise to a range of social meanings and interpretations.